2015
DOI: 10.1039/c5ra10380k
|View full text |Cite
|
Sign up to set email alerts
|

Tunable band gap and magnetism of the two-dimensional nickel hydroxide

Abstract: The electronic structures and magnetic properties of two dimensional (2D) hexagonal Ni(OH)2 are explored based on first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…However, significant magnetism is rarely observed in experiment due to the delocalization of s and p orbitals in carbon materials. Alternatively, 2D inorganic graphene-like crystals, such as transition metal dichalcogenides, oxides, nitrides, , carbide, halide, , silicide, and complex ternary compounds, present great opportunities in spintronics applications for the possible existence of d orbital itinerant magnetism transition metal atoms and coupling between them.…”
Section: Methodsmentioning
confidence: 99%
“…However, significant magnetism is rarely observed in experiment due to the delocalization of s and p orbitals in carbon materials. Alternatively, 2D inorganic graphene-like crystals, such as transition metal dichalcogenides, oxides, nitrides, , carbide, halide, , silicide, and complex ternary compounds, present great opportunities in spintronics applications for the possible existence of d orbital itinerant magnetism transition metal atoms and coupling between them.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10] The emergence of magnetism in 2D materials usually needs external electric eld, edgefunctionalizing, vacancy, defect, strain and doping. 8,11,12 Experimentally, substitutional doping has been proved to be Fig. 1 The schemes of density of states n(E) as a function of energy E for (a) a half-metal and (b) a half-semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the valance of Ni can undergo progressive oxidation from Ni II to Ni III/IV , [26][27][28] which promotes the O 2 generation rate greatly, and the promotional mechanism of Ni(OH) 2 for photocatalytic OER coupled with TiO 2 has been confirmed. [29] Thus, Ni(OH) 2 is suitable for the optimal O 2 evolution. [29] Thus, Ni(OH) 2 is suitable for the optimal O 2 evolution.…”
Section: Black Phosphorus-based Compound With Few Layers For Photocatmentioning
confidence: 99%
“…Then, a photoassisted approach for loading BP on the surface of Ni(OH) 2 was developed as shown in Figure S1. [26][27][28][29] During above multistep reaction processes, BP in the solution migrates to the surface of Ni(OH) 2 , where it is loaded tightly because of the interaction resulting from the oxidation of Ni II to Ni III/IV by the holes of BP ( Figure S3 and S4). After that, the mixture was irradiated under light irradiation, BP would produce electrons and holes, which then reduced protons to H 2 and oxidized water to O 2 ( Figure S2), respectively.…”
Section: Black Phosphorus-based Compound With Few Layers For Photocatmentioning
confidence: 99%